Acoustic radiation force impulse sonography‐based noninvasive prediction of cirrhosis and esophageal varices. Issue 2 (3rd April 2019) - Wang, Chi‐Chih; Tsai, Ming‐Chang; Lin, Ching‐Pin; Chang, Ming‐Hui; Yang, Tzu‐Wei; Tsai, Chia‐Hsun; Chen, Kwei‐Ming; Yeo, Kai‐Fuan; Chen, Hsuan‐Yi; Lin, Chun‐Che
Abstract : Esophagogastroduodenoscopy (EGD) screening is currently suggested with a practice guideline for all cirrhosis patients, but the true EGD screening rate is low. Our study evaluates noninvasive variables—including liver stiffness (LS), spleen stiffness (SS), and spleen diameter—based on acoustic radiation force impulse (ARFI) sonography for noninvasive prediction of cirrhosis and esophageal varices (EVs). In our study, 118 patients (mean age 57.11 ± 11.23), who were classified into a cirrhosis group and a chronic liver disease group, were compared statistically on their blood data and ARFI sonography. To identify the most effective variable for noninvasive prediction of EVs, the cirrhosis group was further divided into two subgroups by the presence or absence of EVs. EV and non‐EV (NEV) patients were compared statistically using blood data, spleen diameter, LS, and SS. The LS cutoff value for predicting cirrhosis was determined as 1.64 m/s, which carried a sensitivity of 81.2% and a specificity of 93.9%. SS and spleen diameter met a significant difference for EV prediction. Spleen diameter with a cutoff value of 10.69 cm carried a sensitivity of 96.2% and a specificity of 56.3%; SS with a cutoff value of 2.82 m/s carried a sensitivity of 96.2% and a specificity of 50%. In our study, a new cutoff criterion composed of spleen diameter and SS was suggested as a better clinical tool for the screening of EVs.